Effect of Tetraethoxysilane Addition to Coconut Coir Ash Nanosilica on Morphology and Particle Size of SiO2-TiO2 Nanocomposite - Triana Dwi Restika; Ratnawulan, Ratnawulan (Department of Physics, Universitas Negeri Padang, 2024)
Nanotechnology is not possible without nano-sized materials. Nanomaterials can be used to produce composites that can be used in various fields, including in industry as fabric coating materials by providing certain properties to fabrics, one of which is water repellent properties. By adjusting the shape and size of the microscopic elements that comprise the nanocomposite, these water-repellent characteristics may be changed, changing the surface morphology, and interacting with the particles through the incorporation of two or more materials. Therefore, the goal of this research is to ascertain how the effect of tetraethoxysilane as a co-precussor SiO2 and as coupling agent on the SiO2-TiO2 nanocomposite layer. This type of research is experimental. Starting with the grinding of coconut fiber ash using HEM-E3D, the experiment continued with the extraction of silica using the sol-gel method and checking its composition with XRF. Next, the prepared nanocomposites were applied to the fabric. Furthermore, the nanocomposites were characterized by SEM and contact angle testing was conducted. The results of this study show that nanocomposites have better properties than their constituent particles. With the variation of adding 7 milliliters of tetraethoxysilane, the smallest particle size reaches 51 nm, and produces the best contact angle of 148°.